Developing the Urban Transportation Business Model (Case Study: Restructuring Business Model of PDJT Transpakuan Bogor) - Widya Ayuningtyas, Dwi; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2017)
Abstract - The condition of the transportation system in Bogor faces many challenges, particularly in managing the traffic system, harmonizing the transportation modes, and also tackling the social as well as economic issues. As the regional government who has obligation to manage the urban transportation in Bogor, the Government of Bogor City established the regional owned company, PDJT TransPakuan as a company who has vital roles in servicing the public transportation in Bogor City and also expected to be one source of Pendapatan Asli Daerah (PAD). However, from its establishment until now, the condition of PDJT TransPakuan never recorded profit because of some challenges that they faced. Therefore, the purpose of this research is to help PDJT TransPakuan solving their problem to increase their performance both in service aspect and financial aspect. This research is using qualitative and quantitative approach to identify the problems and to define the solution for PDJT TransPakuan, in this research the unit business that would be restructured is TransPakuan city bus. The qualitative approach used to identify the factors that influencing the company by interview the experts consist of the director of the company and the urban transportation consultants. Afterward, the quantitative approach used to make scoring of those factors. The methods that used in this research are PEST (Political, Economic, Social, and Technological) analysis, Porter’s Five Forces analysis, resources analysis, rootcause analysis, and SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. Furthermore, defining the strategies by using the TOWS matrix based on the result from SWOT analysis. The strategies which generated from the TOWS matrix used to develop proposed new business model. The analysis of financial performance and the projection also been made as a verification that the proposed new business model will work well and fit to the company. The result shows that to become a sustainable company, PDJT TransPakuan should improve their performance by restructuring their business model and applying the strategies as a solution to solve the problems and achieve the goals. The company should have a commercial mindset, not only focusing on the service. Based on the assessment, the appropriate new business model to the company is developing new route and add more buses, partnering with third parties for the advertising business, and renting out the spot location for ducting fiber optic. By running this kind of business model, as shown in the financial projection, TransPakuan could increase the revenue and could minimize the subsidy from the government of Bogor. Furthermore, PDJT TransPakuan will become a profitable company. So that, the company should apply the strategies as well as the new businesses and then monitor the implementation continuously.Keywords: urban transportation, business restructuring, business model canvas